Intraoral lipoma: a rare clinical entity - Agarwal, Rashmi (BMJ Publishing Group, 2013)
Lipoma is a painless soft tissue tumour of the mesenchymal origin, which is slow growing and well circumscribed. The occurrence of lipoma is rare in the oral cavity (1–4%); however, the frequency is much higher in the head and neck region. The tumour is mostly present in the buccal mucosa, lips, tongue, palate, buccal sulcus and floor of the mouth. Sometimes the tumour becomes large enough to cause difficulty in speech and mastication. Histologically, lipoma is composed of mature fat cells, surrounded by normal fat. We present two cases of intraoral lipoma in two female patients.